Pengembangan Bahan Ajar Berbasis Pendidikan Karakter Dalam Mendukung Implementasi Kurikulum 2013 - Mumtazah Maulida; Mustika Wati; Syubhan An'nur (Universitas Lambung Mangkurat, 2015)
The purpose of education in Indonesia is creating someone who is not only qualified but also has character. This is consistent with the base conceptual of the curriculum 2013which based on competency and character. To support this research was conducted to develop teaching material based character education that specifically aimed to: (1) describe the validity of developed teaching material, (2) describe the achievement of students on the desired character, and (3) describe the response of students to the developed teaching material. This research is a research and development which is referred to the model of learning development Kemp. The subject of this research are 32 students of VII D class in Junior High School 31 Banjarmasin. Data is collected using the result of pretest, validity paper of teaching-learning, observation paper for the character, and student’s response questionnaire. The teaching material on the thermal expansion based character education is valid with little revision and can made the students achieve the desired character and also got the positive response by students with the category is very well. This case be brace that the teaching material developed able to support the implementation of curriculum 2013, which is curriculum based character and competency.